“Você deve voltar e enfrentar as batalhas que são seu direito de nascença britânica, Carole, como uma verdadeira nigeriana”: Divisões geracionais diaspóricas em Girl, Woman, Other de Bernardine Evaristo - Santos Brigida, Marcela (Cadernos de Pós-Graduação em Letras, 2022)
This paper looks at Bernardine Evaristo’s treatment of themes relevant to Diaspora Studies, such as generational divides between first- and second-generation immigrants, belonging, and national identity, in her 2019 novel Girl, Woman, Other. For this analysis, I have focused on the relationship between Bummi, a Nigerian mathematician, and her daughter Carole, an investment banker born in England. I propose that Evaristo’s narrative technique favours a reading of the complex dynamics that runs through such relationships by making each character a protagonist of their narrative, thus shedding light on and producing complex subjectivities.